The Importance Of The Principle Of “Maqasid AsShariah” In Islamic Law - Saidahmadkhon GAYBULLAEV (Open Academia, 2025)
The article provides information about the concept of maqasid ash-shari’a (goals of the Shari’a) in Islamic law, its structure, and working mechanisms. Also, the stages of formation of this concept as an auxiliary science in Islamic law are highlighted.
Keywords: maqasid ash-shar’ia; zaruriyat; hajiyat